Examination of novel diagnostic approaches and contemporary strategies for preventing acute mountain sickness - Olejarz, Zuzanna; Nowak, Karolina; Drygała, Zuzanna; Wyrwał, Julia; Zielińska, Zuzanna; Słowik, Magdalena; Nowak, Karolina; Nieć, Maria; Gierlach, Katarzyna; Krasuska, Martyna (Journal of Education, Health and Sport, 2024)
Introduction and purpose: Acute mountain sickness is caused by hypoxia, of which the brain is the most sensitive. The frequency of occurrence at altitudes above 2500 m above sea level may reach up to 75% of travelers. Prevention of altitude sickness mainly concerns the travel plan and pharmacology. Our study aimed to assess the current literature on altitude sickness, and discuss the possible pathophysiology, epidemiology, and symptoms. Moreover, we underline new guidelines for the treatment, prevention, and diagnosis of altitude sickness in the context of the last guidelines and research. We conducted a PubMed literature review using keywords like "mountaineering sickness" and "altitude sickness". All article types were taken into account: clinical trial, meta-analysis, case report, case series, systematic review, randomized controlled trial, observational study, clinical study, books, and documents in the last 5 years.A brief description of the state of knowledge: In recent years, there has been a surge in the accessibility and popularity of high-altitude tourism, emphasizing the need to disseminate information about altitude sickness among travelers. This heightened accessibility has sparked a push for comprehensive research and viable solutions, aiming to address the ramifications of the increased risk associated with such endeavors. Furthermore, there’s a growing call for additional research focusing on the unique medical demands posed by tourist excursions and extreme expeditions. Conclusions:It underscores the necessity for healthcare professionals equipped with specialized knowledge and expertise in both preventing and treating medical conditions arising in exceptional circumstances.